Logistic model of the dynamics of the mycelial growth of the fungus ‘Totolcozcatl’ in culture media - Buendía-Espinoza, Julio Cesar; Álvarez-Sánchez, María Edna; Mateo-Guzmán, Natalia; Bandalá Muñóz, Víctor Manuel; Maldonado-Torres, Ranferi (Revista Mexicana de Ciencias Agrícolas, 2020)
Edible wild mushrooms are considered a non-timber forest resource, of nutritional, ecological, cultural and economic importance for rural communities. In the mountain mesophilic forest, in Xaltepuxtla, Puebla, the looting and overexploitation of the Entoloma abortivum species, known as ‘Totolcozcatl’, place it as a threatened species. Therefore, the objective of this work was to evaluate its dynamics of average mycelial growth, in culture media using a logistic model, for its induction process. The culture media evaluated in 2018 were: malt extract-yeast extract-polypeptone-agar (MYPA); meat peptone-dextrose-yeast extract-bacteriological agar (CYM) and malt-bran extract (EMS). Statistical analysis indicated that the MYPA and EMS substrate were statistically different from CYM (p< 0.05), in mycelial growth after 16 days of culture. The logistic model adjusted to the experimental data obtained in each of the substrates yielded R2 coefficients of determination of 0.99. The model showed that the maximum predicted growth was observed in the EMS substrate (95.94 mm) and the minimum in CYM (83.23 mm). The point of maximum growth and excessive production of hyphae added to the mycelium was obtained in the EMS substrate (47.97 and 9.59 mm), followed by MYPA (45.76 and 8.83 mm) and CYM (41.61 and 6.86 mm). Finally, it is concluded that the main important and viable alternative to the induction process of the Totolcozcatl fungus is the EMS medium.
Keywords: Entoloma abortivum (Berk. & Curtis) Donk.; culture media; growth rate